Peran Mediasi Penerapan E-Wallet Qr-Code Terhadap Perilaku Pengguna - Dinda Ayu Sieradianto Angelia; Ananda Fadia Indah Ramadhani; Nikken Nur Fanydia Ningsih (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
Life continues to evolve in a more modern direction along with technological advancements. Digital transformation plays a crucial role in influencing consumer behavior and societal habits. In Indonesia, the financial sector leads in technological development, particularly in payment methods. The advancement of financial technology in Indonesia indicates that society has adapted and developed innovations in this field. In response to this growth, Bank Indonesia has introduced a policy to implement a single QR code that can be used across various payment applications, known as the Quick Response Indonesian Standard (QRIS). In payment methods, the QR Code functions as a connector between users and transaction services. One of the benefits of non-cash payment technology is improving the payment ecosystem and enhancing payment service efficiency across sectors. The objective of this study is to examine the mediating role of QR-Code E-Wallets on User Behavior. This research utilizes SmartPLS version 3.2 as an analytical tool, with SEM methodology and a quantitative survey technique. The findings indicate that performance expectancy, social influence, and hedonic motivation significantly influence the intention to use QR wallets. Additionally, performance expectancy and social influence have a positive and significant impact on User Behavior, while hedonic motivation has a positive but not significant effect on User Behavior. Furthermore, QR-Wallet intention can mediate the influence of hedonic motivation, performance expectancy, and social influence on User Behavior.